Olmesartan medoxomil self-microemulsifying drug delivery system reverses apoptosis and improves cell adhesion in trinitrobenzene sulfonic acid-induced colitis in rats - Hussam Murad; Osama Ahmed; Thamer Alqurashi; Mostafa Hussien (Taylor & Francis Group, 2022)
Olmesartan medoxomil (OM) is an angiotensin receptor blocker. This study aimed to investigate the effects of OM self-microemulsifying drug delivery system (OMS) in trinitrobenzene sulfonic acid (TNBS)-induced acute colitis in rats. Besides two control groups, five TNBS-colitic-treated groups (n = 8) were given orally sulfasalazine (100 mg/kg/day), low and high doses of OM (3.0 and 10.0 mg/kg/day) (OML and OMH) and of OMS (OMSL and OMSH) for seven days. A colitis activity score was calculated. The colon was examined macroscopically. Colonic levels of myeloperoxidase, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), malondialdehyde, and reduced glutathione were measured. Plasma and colonic olmesartan levels were measured. Colonic sections were subjected to hematoxylin and eosin staining and immunohistochemical staining for E-cadherin, caspase-3, and matrix metalloproteinase-9 (MMP-9). Protein expression of E-cadherin, Bcl-2 associated X protein (Bax), and B-cell lymphoma 2 (Bcl-2), and cleaved caspase-3 by Western blot was done. TNBS-colitic rats showed increased colonic myeloperoxidase, TNF-α, IL-6, and malondialdehyde, decreased colonic glutathione, histopathological, immunohistochemical, and protein expression alterations. OMS, compared with OM, dose-dependently achieved higher colonic free olmesartan concentration, showed better anti-inflammatory, antioxidant, and anti-apoptotic effects, improved intestinal barrier, and decreased mucolytic activity. OMS more effectively up-regulated the reduced Bcl-2, Bcl-2/Bax ratio, and E-cadherin expression, and down-regulated the overexpressed Bax, cleaved caspase-3, and MMP-9. OMSL exerted effects comparable to OMH. Sulfasalazine exerted maximal colonic protective effects and almost completely reversed colonic damage, and OMSH showed nearly similar effects with non-significant differences in-between or compared with the normal control group. In conclusion, OMS could be a potential additive treatment for Crohn's disease colitis.